Review, analysis, and optimization of the CRISPR Streptococcus pyogenes Cas9 system - Guohua Wang; Juan Li (Elsevier, 2021)
Despite certain defects hindering its clinical application, the CRISPR (clustered regularly interspaced short palindromic repeats)-associated (Cas) Streptococcus pyogenes Cas9 (spCas9) system is the most studied and the most popular tool for genome editing. The mechanism underlying the action of the spCas9 system forms the critical base required for rational optimization. To further our understanding of the underlying mechanisms and to optimize the spCas9 system, we investigated and analyzed the following aspects: 1) the origin of the power promoting domain movement for initiating cleavage; 2) the mechanism underlying the searching and unwinding of the target DNA; 3) the key domains of spCas9 and their functions; and 4) the molecular mechanism of the cleavage reaction. We speculated that: 1) the extruded sgRNA-DNA hybrid extrusion is the original force promoting domain movement; 2) electrostatic interactions lead to a combination of spCas9 to sgRNA, and the hydrophobic environment is the key factor for melting the double-stranded DNA; 3) the REC2 domain could be removed; and 4) the cleaving basis of spCas9 is the Mg2+-dependent SN2-like reaction. This study will be helpful for systematically understanding and optimizing the spCas9 system.